EXTRACTED PEARL GRASS EFFECT ON BROILER CARCASS KEPT ON Escherichia coli – SPRAYED LITTER - Nurhayati, N.; Latief, M.; Insulistyowati, A. (Diponegoro University, 2010)
An experiment was conducted to determine the effect of hexane and acetic ethyl extracted pearlgrass as feed additive in the ration on carcass of broiler chickens where the litter was sprayed byEscherichia coli. The experiment was assigned to Completely Randomized Design with 5 treatmentsand 4 replications. The treatments were level of pearl grass extract added into the ration; 0 (R0, control),0.8 (R1), 1.6 (R2), 2.4 (R3) dan 3.2 (R4) gram per kilogram ration. After 3 weeks of age, litters weresprayed by Escherichia coli as much as 106 CFU/100 ml liquid agar. Then, chickens were kept until 6weeks of age. Result showed that there was no significant different among treatments groups on chickencarcass and there was no any adverse effect on liver and intestines. It is concluded that extracted pearlgrass could be utilized as natural feed additive source to produce carcass of broiler chicken where theirlitter was sprayed by E. coli bacteria.